Acute effects of dapagliflozin on renal oxygenation and perfusion in type 1 diabetes with albuminuria: A randomised, double-blind, placebo-controlled crossover trial. (July 2021) - Laursen, Jens Christian; Søndergaard-Heinrich, Niels; de Melo, Joana Mendes Lopes; Haddock, Bryan; Rasmussen, Ida Kirstine Bull; Safavimanesh, Farzaneh; Hansen, Christian Stevns; Størling, Joachim; Larsson, Henrik Bo Wiberg; Groop, Per-Henrik; Frimodt-Møller, Marie; Andersen, Ulrik Bjørn; et al.
Abstract: Background: Inhibitors of the sodium-glucose cotransporter 2 (SGLT2) slow the progression of diabetic kidney disease, possibly by reducing the proximal tubule transport workload with subsequent improvement of renal oxygenation. We aimed to test this hypothesis in individuals with type 1 diabetes and albuminuria. Methods: A randomised, double-blind, placebo-controlled, crossover trial with a single 50 mg dose of the SGLT2 inhibitor dapagliflozin and placebo in random order, separated by a two-week washout period. Magnetic resonance imaging (MRI) was used to assess renal R2 * (a low value corresponds to a high tissue oxygenation), renal perfusion (arterial spin labelling) and renal artery flow (phase contrast imaging) at baseline, three- and six hours from tablet ingestion. Exploratory outcomes, including baroreflex sensitivity, peripheral blood oxygen saturation, peripheral blood mononuclear cell mitochondrial oxygen consumption rate, and biomarkers of inflammation were evaluated at baseline and 12 h from medication. The study is registered in the EU Clinical Trials Register (EudraCT 2019–004, 557–92), on ClinicalTrials.gov (NCT04193566), and is completed. Findings: Between February 3, 2020 and October 23, 2020, 31 individuals were screened, and 19 eligible individuals were randomised. Three dropped out before receiving any of the interventions and one dropped out after receiving only placebo. We included 15 individuals (33% female) in the per-protocol analysis with a mean age of 58 (SD 14) years, median urinary albumin creatinine ratio of 46 [IQR 21–58] mg/g and an eGFR of 73 (32) ml/min/1·73m 2 . The mean changes in renal cortical R2 * from baseline to six hours were for dapagliflozin -1·1 (SD 0·7) s −1 and for placebo +1·3 (0·7) s −1, resulting in a difference between interventions of -2·3 s −1 [95% CI -4·0 to -0·6]; p  = 0·012. No between-intervention differences were found in any other MRI outcomes, physiological parameters or exploratory outcomes. There were no adverse events. Interpretation: A single dose of 50 mg dapagliflozin acutely improved renal cortical R2 * without changing renal perfusion or blood flow. This suggests improved renal cortical oxygenation due to a reduced tubular transport workload in the proximal tubules. Such improved oxygenation may in part explain the long-term beneficial renal effects seen with SGLT2 inhibitors, but it remains to be determined whether the observed effects can be achieved with lower doses, with chronic treatment and if they occur in type 2 diabetes as well.